Britain's anti-terror laws: Consequences for civil liberties and the integration of British Muslims - Sabine Riedel (Stiftung Wissenschaft und Politik (SWP), 2005)
On October 12, in the wake of the London bomb attacks of July 7 and 21, 2005 the British government presented a bill that is supposed to tighten up existing counter-terrorism legislation. Critics from the ranks of the Liberal Democrats want clarification on whether the draft text fulfils international human rights standards. They are accusing the Labour government of disregarding basic civil rights such as freedom of speech and freedom of expression.Regardless of that it must be examined what kind of repercussions the legislation and the recent anti-terror measures have on the integration of Muslim immigrants. After all, in the long run these can only be successful if they are in accord with a basic principle of integration policy: respecting the immigrants' religiosity. However, that respect must end where religion is drafted in to serve dangerous political ends. That the problems concerning the integration of Muslims have grown since the bomb attacks, can already be seen by the number of racially motivated acts of violence: after July 7, 2005 this figure increased sevenfold within a month in London alone. (SWP Comments / SWP)
Keywords: 320